2013
DOI: 10.1590/s1517-83822013000100033
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol production from rice straw residues

Abstract: A rice straw - cellulose utilizing mold was isolated from rotted rice straw residues. The efficient rice straw degrading microorganism was identified as Trichoderma reesei. The results showed that different carbon sources in liquid culture such as rice straw, carboxymethyl cellulose, filter paper, sugar cane bagasse, cotton stalk and banana stalk induced T. reesei cellulase production whereas glucose or Potato Dextrose repressed the synthesis of cellulase. T. reesei cellulase was produced by the solid state cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(63 citation statements)
references
References 38 publications
2
53
1
3
Order By: Relevance
“…World annual rice straw production is estimated to be >950 million tons and, currently, most of these were utilized for feeding cattle, and still a large portion of the rice straw biomass is burnt in the agricultural fields without much usage, thus not only causing environmental concerns like air pollution but also adversely affecting the health hazard issues for humans (Liu et al 2011;Binod et al 2010). However, it is estimated that this amount of rice straw can potentially produce approximately 205 billion liters of bioethanol annually, which is the largest amount from a single biomass feedstock (Belal 2013). Like other lignocellulosic residues, the main contents in rice straw are cellulose (32-47 %), hemicellulose (19-27 %), and lignin (5-24 %).…”
Section: Introductionmentioning
confidence: 99%
“…World annual rice straw production is estimated to be >950 million tons and, currently, most of these were utilized for feeding cattle, and still a large portion of the rice straw biomass is burnt in the agricultural fields without much usage, thus not only causing environmental concerns like air pollution but also adversely affecting the health hazard issues for humans (Liu et al 2011;Binod et al 2010). However, it is estimated that this amount of rice straw can potentially produce approximately 205 billion liters of bioethanol annually, which is the largest amount from a single biomass feedstock (Belal 2013). Like other lignocellulosic residues, the main contents in rice straw are cellulose (32-47 %), hemicellulose (19-27 %), and lignin (5-24 %).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, acid-pretreated rice straw had a lower ethanol production of 10 g/L (Belal 2013). An ethanol concentration of 3.8 g/L was obtained from microalgae by optimizing AP pretreatment conditions and the SSF approach (Harun et al 2010).…”
Section: Simultaneous Saccharification and Fermentation (Ssf)mentioning
confidence: 87%
“…Belal (2013) reported that the optimum pH for PHB hydrolase was at pH7, a second optimum pH appeared at pH 6 on agar plates. It is known also that the optimum pH for growth of Thermobifida fusca or T. bispora on mineral salt medium with glucose was pH 7.…”
Section: Discussionmentioning
confidence: 99%